Walking the Tightrope: Populist Radical Right Parties’ Framing of ‘Good’ and ‘Bad’ Migrants in Belgium and Switzerland - Sijstermans, Judith; Favero, Adrian (Politics of the Low Countries, 2025)
In this article, we look in detail at two populist radical right (PRR) parties’ framing and discourse around a key ideological area for PRRPs: migration and migrants. PRRPs have succeeded in agenda-setting around these issues, which have been a source of their electoral success. However, parties’ framing of these issues has also been a place for vagueness, through ‘doublespeak’ and euphemizing. Building on over 100 interviews with party representatives and members in Belgium and Switzerland, we investigate how the Swiss People’s Party (in government) and the Vlaams Belang (in opposition) portray migrants. In both cases, parties frame some migrants as ‘good’ and others as ‘bad’ based on cultural and economic criteria. This differentiation is enabled by euphemistic, unclear language. Parties’ substantive formulation of who fits into the ‘good’ and ‘bad’ migrant criteria differs. However, for both parties this differentiated portrayal of migrants reflects the need to walk a tightrope between moderate reputations and radical credentials on the key issue of nativism.